Achievements And Challenges Of Out-Of-School Education (On the example of Barkamol Avlod children’s schools in Fergana region) - Maksuda Badalova (Zien Journals, 2021)
This article focuses on the study of the activities of Barkamol Avlod1 children's schools. The work, achievements, and shortcomings of the Barkamol Avlod children's schools in Fergana region have been studied. The data of pedagogical staff, to increase the number of circles, the level of coverage of children have been analyzed and relevant suggestions and conclusions have been made.
Keywords: Harmoniously developed generation; Law; order; circles